Pendampingan Pembuatan Katalog Produk pada UMKM Batik Sekar Rinambat sebagai Media Pemasaran: Assistance in Creating Product Catalogs for UMKM Batik Sekar Rinambat as a Marketing Tool - Agustino, Muhammad; Kustaji, Kustaji; Noor, Fauzian; Citrapati, Mugito (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
MSME problems lie in the strategy and limitations of marketing methods. This activity is a collaborative effort aimed at increasing product awareness and sales. UMKM Sekar Rinambat was founded in 2021 with traditional Bojonegoro batik products. Until now, we still face challenges in penetrating a more comprehensive market because we don't use the proper marketing methods. This service activity focuses on assistance in creating product catalogs; marketing strategies can be improved. Product catalogs act as a communication tool facilitating product exposure to potential consumers. This catalog is an effective medium for expanding market reach by presenting clear and exciting information. This assistance provides double benefits: first, introducing the product to a broader market, and second, providing MSMEs with a better understanding of effective marketing procedures. Through this approach, public awareness of MSME products can be increased significantly, which is expected to increase sales. Using the Participatory Action Research (PAR) method allows the service team to understand and be able to provide mentoring on target. The results of this assistance help create product photos and provide a strong foundation for business development and growth at local and regional levels. Catalog creation can also be used as a tool for digital marketing through e-catalogs to increase product sales.